"I Made a Choice": Enrico Taglietti Citizen of the World in Canberra. Issue 3 (1st September 2020) - Micheli, Silvia
ABSTRACT: When Italian architect Enrico Taglietti landed in Sydney for the first time in 1955, he had no idea he would become one of the most acclaimed architects of Australia. The reason for his first trip to Sydney was the invitation to curate a commercial display of Italian design to be held at the country's most famous department store, David Jones. Taglietti decided to set up his career in Australia after discovering Canberra, a city that he found inspiring and full of opportunities: a unique condition of tabula rasa. In 2007, Taglietti was awarded the Gold Medal of the Royal Australian Institute of Architects, becoming the second Italian-born architect to receive such an honour. This essay unpacks Taglietti's move from Milan to Canberra, discussing his background, motivations, ambitions and vision for the capital city of Australia. The paper focuses in particular on the circumstances in which he discovered Canberra, critically positioning him as a "citizen of the world" – an expression he used referring to himself. In so doing, this paper adds a layer of complexity to the discourse of 20th century Australian émigré architects, considering the case of an Italian architect whose relocation to Australia was a deliberate choice.